Holistic assertiveness skills for nurses : empower yourself and others - Clark, Carolyn Chambers (Springer Pub., 2003)
This guide to assertiveness skills for nurses is designed to meet the needs of individual nurses, and for classroom and workshop use. Nurses can also use the many exercises in the book with their patients to help them find more assertive and empowered ways to react and be proactive. The author's premise is that assertiveness is a skill, like giving an injection or taking a nursing history, which requires adequate and systematic practice. It also should be viewed within the context of one's own health and well-being. The workshop format encourages readers to assess and build their skills throug.